Endophytic Enterobacter cloacae exhibits antagonistic activity against Pythium damping-off of cucumber - Kazerooni,Elham Ahmed (2020)
ABSTRACT: The study was performed to examine the potential presence of biological control agents against Pythium damping-off disease of cucumber.Examining eleven bacterial strains isolated from acid lime roots and rhizosphere soil showed that the bacterial strain RB1 was the most efficient in suppressing mycelial growth of P. aphanidermatum, producing an inhibition zone of 5mm. Scanning electron microscopy study of the mycelia at the interaction zone showed that the pathogen hyphae were deformed and shriveled by the bacterial strain.In pot experiments, pretreatment with the RB1 bacterial strain reduced disease incidence significantly by 63%.The bacterial strain did not exhibit any negative significant effects on cucumber growth (plant height and root dry weight) in comparison with untreated control under growth chamber conditions. Molecular identification of strain RB1 based on the 16S rRNA gene revealed that it is Enterobacter cloacae. Findings from this study suggested that E. cloacae has a potential to be used as a biocontrol agent for suppressingcucumber damping-off disease caused by P. aphanidermatum. This is the first report of the antagonistic activity of E. cloacae against P. aphanidermatum-induced damping-off of cucumber.